2021
DOI: 10.3390/nano11092423
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Carbon-Assisted Chemical Vapor Deposition Growth of Large-Area Uniform Monolayer MoS2 and WS2

Abstract: Monolayer MoS2 can be used for various applications such as flexible optoelectronics and electronics due to its exceptional optical and electronic properties. For these applications, large-area synthesis of high-quality monolayer MoS2 is highly desirable. However, the conventional chemical vapor deposition (CVD) method using MoO3 and S powder has shown limitations in synthesizing high-quality monolayer MoS2 over a large area on a substrate. In this study, we present a novel carbon cloth-assisted CVD method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…71,82,83 The synthesis of 2D MoS 2 by CVD approaches involve decomposition and annealing of precursors like (NH 4 ) 2 MoS 4 , ammonium heptamolybdate (AHM), thiourea, sulphur powder and MoO 3 at high temperature, the precursors consists of both metal (Mo) and chalcogen (S) elements. 27,71,[84][85][86][87][88][89] The decomposition of precursors takes place under reductive and inert environment, to eliminate oxidation and enhance the conversion of precursor into MoS 2. 83,90 To undergo reaction between the precursor (Mo and S) and to synthesize MoS 2 , the precursor should be heated to sufficient and optimal conditions (often very high temperatures > 700 °C).…”
Section: Bottom-up Synthesis Of Two-dimensional Molybdenum Disulphidementioning
confidence: 99%
See 1 more Smart Citation
“…71,82,83 The synthesis of 2D MoS 2 by CVD approaches involve decomposition and annealing of precursors like (NH 4 ) 2 MoS 4 , ammonium heptamolybdate (AHM), thiourea, sulphur powder and MoO 3 at high temperature, the precursors consists of both metal (Mo) and chalcogen (S) elements. 27,71,[84][85][86][87][88][89] The decomposition of precursors takes place under reductive and inert environment, to eliminate oxidation and enhance the conversion of precursor into MoS 2. 83,90 To undergo reaction between the precursor (Mo and S) and to synthesize MoS 2 , the precursor should be heated to sufficient and optimal conditions (often very high temperatures > 700 °C).…”
Section: Bottom-up Synthesis Of Two-dimensional Molybdenum Disulphidementioning
confidence: 99%
“…Due to their remarkable chemical and optical properties, 2D MoS 2 materials are the most studied materials amongst other TMD materials. [26][27][28] 2D MoS 2 has garnered a lot of research interest recently and this is evidenced in the exponentially increasing publication numbers. [29][30][31] Figure 1 shows the number of publication of 2D MoS 2 materials indicating the rising trend of interest in 2D MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…During the WS 2 film growth the substrate has a significant impact concerning the film quality and topography. Most of the studies have been performed on amorphous SiO 2 [21,22], sapphire model substrates [23][24][25][26][27] and graphene/HOPG [28,29]. Recently, on W-Au alloy substrate Wang et al demonstrated a strategy for preferentially forming antisite defects during WS 2 growth [30].…”
Section: Introductionmentioning
confidence: 99%